Obtenção e utilização de grafos-limite de autômatos celulares elementares - Ruivo, Eurico Luiz Prospero (2016)
Cellular automata are locally de ned dynamical systems which are discrete in space, time and in the state variables, and capable of presenting arbitrarily complex global emergent behaviour. One core question in the study of cellular automata refers to their limit behaviour, that is, to the global dynamical features in a in nite time evolution. Previous works have shown that for nite time evolutions, one-dimensional cellular automata present dynamics which can be described by regular languages and, therefore, by nite automata. Also, such studies have shown the existence of growth patterns in the evolution of such nite automata for some cellular automata rules; however these results were obtained manually by directly inspecting the structures that arise during the time evolution. In this work we present the formalisation of an automatic method to compute such structures. Based on this, the rules of the elementary cellular automata rule space were classi ed according to the existence of a growth pattern in their nite automata. Also, we present new methods to infer the limit graph of some elementary cellular automata rules by analysing the regular expressions describing their behaviour in nite-time and the attractors of each rule, as well as an application of these graphs in computing the Fourier spectra of the rules.